The impact of Kersen leaves (Muntingia calabura L.) extract on Mus musculus with hypercholesterolemia - Sion Benu; Anita Amat; Arley Telussa; Rr Listyawati Nurina (Acta Biochimica Indonesiana)
Background: Hyperlipidemia, a condition marked by elevated levels of total cholesterol and related lipids, poses significant health risks. The potential cholesterol-lowering effects of Kersen leaves (Muntingia calabura L.), which are rich in flavonoids, saponins, and tannins, warrant investigation. Despite the recognized benefits of Muntingia calabura L., its potential, particularly from the Nusa Tenggara Timur (NTT) region, still needs to be explored.